Development of Rotating Screen Grader for selected orchard crops - Narvankar, Deepali S; Jha, S K; Singh, Amar (Journal of Agricultural Engineering, 2005)
A rotating screen grader suitable for fruits like lemon, ber, aonla was developed in to grade the samples in 4 grades. The grader was tested for capacity and optimum grading performance as a function of rotating speed of screen, diameter of screen, exposure length and input each at four levels by using second order response surface design in 80 design points. Capacity of the grader varied from 45 to 327.27 kg/h for lemon, 43.63 to 464.51 kg/h for aonla and 46.75 to 436.36 kg/h for ber. The maximum grading efficiency for lemon, aonla and ber was found to be 79, 93.8 and 97.96%, respectively.